The ceramide pathway is involved in the survival, apoptosis and exosome functions of human multiple myeloma cells in vitro - CHENG Qian; LI Xin; WANG Yue; DONG Min; ZHAN Feng-huang; LIU Jing (Acta Pharmacologica Sinica, 2018)
Abstract Multiple myeloma (MM) is characterized by the clonal proliferation of malignant plasma cells and refractoriness to traditional therapies. It has been shown that exosomes are involved in modulating the progression and the metastasis of cancers through microRNAs (miRs). Ceramide is a type of sphingolipid; the ceramide pathway of exosomal secretion has been shown to affect the apoptosis of cancer cells. But the role of this pathway in MM cell function, exosome function and miR regulation remains unknown. In this study, we showed that C6 ceramide (an exogenous ceramide supplement, 1.25–40 μmol/L) dose-dependently inhibited the proliferation and promoted the apoptosis in human MM OPM2 cell line, which were associated with elevated caspase 3/9 and PARP cleavage. We also found that C6 ceramide (5–20 μmol/L) dose-dependently stimulated exosome secretion and increased exosomal levels of tumor-suppressive miRs (miR 202, miR 16, miR 29b and miR 15a). Of note, exosomes from C6 ceramide-treated OPM2 cells could influence the proliferation and apoptosis of the recipient OPM2 cells, which correlated with increased tumor-suppressive exosomal miRs. In contrast, GW4869 (a ceramide inhibitor, 5–20 μmol/L) exerted the opposite effects on the regulation of MM function, exosome secretion and miR levels in MM exosomes. However, exosomes from GW4869-treated OPM2 cells had no effect on these miRs and the survival of targeted OPM2 cells. Taken together, our findings reveal that the ceramide pathway modulates MM survival, probably directly via the caspase pathway and indirectly via exosomal miR mechanisms.